Respostas
respondido por:
30
9y² + 12y + 4 = 0
Δ= b²-4ac
Δ= (12)² - 4.9.4
Δ= 144 - 144
Δ= 0
x= -b+-√Δ / 2.a
x= -12+-√0 / 2.9
x= -12+-0 / 18
x'= -12 + 0 / 18 = -12 / 18 simplificando -2 / 3
x''= -12 - 0 / 18 = -12 / 18 simplificando -2 / 3
respondido por:
5
Nesse caso a=9; b= 12 e c=4
Δ = (-b)² - 4.a.c
Substituindo, temos:
Δ = (-12)² -4.9.4
⇒ Δ = 144- 144
Δ = 0
Nesse caso ; x = -12 +- 0/18
x1= -12/18 ⇒x=-2/3
Δ = (-b)² - 4.a.c
Substituindo, temos:
Δ = (-12)² -4.9.4
⇒ Δ = 144- 144
Δ = 0
Nesse caso ; x = -12 +- 0/18
x1= -12/18 ⇒x=-2/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás